New Insights into the Prevention of Hospital-Acquired Pneumonia/Ventilator-Associated Pneumonia Caused by Viruses - Klompas, Michael (Seminars in Respiratory and Critical Care Medicine, 2022)
A fifth or more of hospital-acquired pneumonias may be attributable to respiratory viruses. The SARS-CoV-2 pandemic has clearly demonstrated the potential morbidity and mortality of respiratory viruses and the constant threat of nosocomial transmission and hospital-based clusters. Data from before the pandemic suggest the same can be true of influenza, respiratory syncytial virus, and other respiratory viruses. The pandemic has also helped clarify the primary mechanisms and risk factors for viral transmission. Respiratory viruses are primarily transmitted by respiratory aerosols that are routinely emitted when people exhale, talk, and cough. Labored breathing and coughing increase aerosol generation to a much greater extent than intubation, extubation, positive pressure ventilation, and other so-called aerosol-generating procedures. Transmission risk is proportional to the amount of viral exposure. Most transmissions take place over short distances because respiratory emissions are densest immediately adjacent to the source but then rapidly dilute and diffuse with distance leading to less viral exposure. The primary risk factors for transmission then are high viral loads, proximity, sustained exposure, and poor ventilation as these all increase net viral exposure. Poor ventilation increases the risk of long-distance transmission by allowing aerosol-borne viruses to accumulate over time leading to higher levels of exposure throughout an enclosed space. Surgical and procedural masks reduce viral exposure but do not eradicate it and thus lower but do not eliminate transmission risk. Most hospital-based clusters have been attributed to delayed diagnoses, transmission between roommates, and staff-to-patient infections. Strategies to prevent nosocomial respiratory viral infections include testing all patients upon admission, preventing healthcare providers from working while sick, assuring adequate ventilation, universal masking, and vaccinating both patients and healthcare workers.
Keywords: hospital-acquired pneumonia; respiratory viruses; nosocomial infection; infection control; masking; ventilation